HISTORY OF THE DATIVE MARKERS IN KOREAN LANGUAGE: FROM OLD KOREAN TO CONTEMPORARY KOREAN - BAILBLÉ, Olivier (International Journal of Korean Humanities and Social Sciences, 2016)
The focus of this paper and the intention of the author are to show in a diachronic perspective how the dative markers in Korean Language have changed and evolved during two thousand years of history. The rise of new writing systems during 8th century such as Idu and also the difference of the structure of the language between Chinese and Korean bring different conclusions. In particular, this paper will focus on the different grammatical origins of dative markers and additionally the morphological changes will be shown in those structures, especially with the rise of the Korean Alphabet in 15th century.